HUBUNGAN ANTARA HARGA DIRI DAN TINGKAT PENDIDIKAN DENGAN SIKAP PENERIMAAN IBU TERHADAP ANAK AUTIS DI YAYASAN I-HOME SCHOOLING MEDAN - Ernita Mariana Ginting; Rahmi Lubis (Analitika: Jurnal Magister Psikologi UMA, 2010)
This study aims to determine and prove the relationship between self-esteem and level of education with an attitude of acceptance of mothers of children with autism. The hypothesis advanced is that there is a positive relationship between self-esteem with an attitude of acceptance of mothers of children with autism, there is a positive relationship between level of education with an attitude of acceptance of mothers of children with autism and there is a positive relationship between self-esteem and level of maternal education with an attitude of acceptance toward the child with autism.            The results showed that there was a significant relationship between self-esteem with an attitude of acceptance of mothers of children with autism by 0039 a significant level <0.05 (5%) with a variable contribution of R ² = 14:28% against acceptance; There is a very significant positive relationship between acceptance level of education with mothers of children with autism by 0000 a significant level <0.01 (1%) with a variable contribution of R ² = 40.19% against acceptance; there is a significant relationship between self-esteem and level of education with an attitude of acceptance mothers   toward children with autism with the acquisition of R ² = 0.474, which means self-esteem and levels of education together can explain the variability of 47.4% and 52.6% influenced by other factors that are not the focus in this study.